As contribuições das plantas medicinais no ensino de biologia: uma proposta de sequência didática para a EJA - Lopes, Richard Suárez (2024)
This study is based on the premise of valuing traditional knowledge and environmental preservation, combining classroom research and using the theme of medicinal plants as a contextualizing support for approaching Biology concepts and content. However, when addressing these concepts, it becomes essential to know the level of understanding of students in relation to school content, in order to build new knowledge. In this sense, the research was guided by the following problematization: how is it possible to address, in the EJA (Youth and Adult Education) curriculum, knowledge about medicinal plants in order to promote a more contextualized Biology teaching? Therefore, the objective of this study was to develop, apply and evaluate a didactic sequence based on the 3MP (Three Pedagogical Moments) that used medicinal plants as a contextualizing theme for approaching Biology concepts in EJA High School in the city of Guajará-Mirim, RO. The research was based on studies by Barros (2020), Delizoicov, Angotti and Pernambuco (2018), Tiago et al. (2020) and others. A qualitative action research was conducted using questionnaires, the researcher teacher's logbooks and activities developed by the students as data collection instruments. The didactic intervention was applied in the Biology discipline, involving eleven EJA High School students in the Modular System of Guajará-Mirim/RO, lasting ten periods. The educational product related to this dissertation is a didactic sequence based on the 3MP, which uses local biodiversity and medicinal plants, such as Jatobá, Copaíba, Mastruz and Quina-Quina as a contextualizing theme for the approach of Biology concepts, specifically arbovirus diseases, such as dengue, zika virus and chikungunya. The application of the didactic sequence demonstrated a satisfactory contribution to the development of the Biology teaching and learning process. This educational product made it possible to awaken students' interest and appreciation for the subject, especially when students see themselves as subjects of this process, appropriating scientific knowledge through empirical knowledge, contributing to the formation of citizens with a critical and reflective sense in society. The teaching material is aimed at Biology teachers and is available for free download on the website of the Graduate Program in Science and Mathematics Teaching at the University of Passo Fundo and on the EduCapes portal, at the link http://educapes.capes.gov.br/handle/capes/742947.